The Frequency of Deixis Used in “I Have A Dream” by Westlife - Tarigan, Ayu Sarmila; Lisdawati, Ida (IKIP Siliwangi, 2025)
Deixis is a term used to represent a word or phrase that directly relates to entities such as objects, processes, attributes, and circumstances. The importance of this research is to find out the frequency and the percentage of deixis that appear in the lyrics of songs to be analyzed by researchers. In addition to knowing this analysis also serves to find out the lyricist's point of view of the song from each deixis contained in the song. The method used in this study was descriptive qualitative. Which data used was based on the data that has been available on the song